Correlations between pollen grain viability and fruit characteristics in ‘Pêra’ sweet orange mutants - Latado, Rodrigo Rocha; Bueno Filho, Julio Silvio Sousa; Pompeu Junior, Jorgino; Tulmann Neto, Augusto (Pesquisa Agropecuaria Brasileira, 2004)
The objective of this work was to evaluate the pollen grain viability of ‘Pêra’ sweet orange mutant plants and to estimate its correlation with fruit characteristics. Mutant plants were obtained from shoot treatment with gamma-rays and selected after three vegetative propagations. Pollen grain viability was evaluated using carmine-acetic staining method. No difference was found between years for pollen grain viability and for number of seeds per fruit, indicating that these characters were not affected by the yearly environmental alterations. Positive correlations were found between pollen grain viability and mean number of seeds per fruit, and with the total soluble solid content in juice. Therefore, one of the reasons for the smaller number of seeds per fruit in these mutants is the low percentage of viable pollen grain.